The German model of industrial relations: (Where) does it still exist? - Michael Oberfichtner; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2017)
Using data from the representative IAB Establishment Panel, this paper charts changes in the two main pillars of the German IR model over the last 20 years. It shows that collective bargaining coverage and worker representation via works councils have substantially fallen outside the public sector. Less formalized and weaker institutions such as voluntary orientation of uncovered firms towards sectoral agreements and alternative forms of employee representation at the work-place have partly attenuated the overall erosion in coverage. Multivariate analyses indicate that the traditional German IR model (with both collective agreements and works councils) is more likely found in larger and older plants, and it is less likely in plants managed by the owner, in single and foreign-owned plants, in individually-owned firms or partnerships, and in exporting plants. In contrast, more than 60% of German plants did not exhibit bargaining coverage or orientation or any kind of worker representation in 2015. Such an absence of the main institutional features of the German IR model is mainly found in small and medium-sized plants, in particular in the service sector and in eastern Germany, and its extent is increasing dramatically. – – Mit Daten des repräsentativen IAB-Betriebspanels zeichnet der Beitrag Veränderungen in den zwei Hauptpfeilern des deutschen Modells der indu-striellen Beziehungen im Lauf der letzten 20 Jahre nach. Er zeigt, dass die Abdek-kung durch Kollektivverhandlungen und die Arbeitnehmervertretung durch Betriebs-räte außerhalb des öffentlichen Sektors stark zurückgegangen sind. Weniger forma-lisierte und schwächere Institutionen wie eine freiwillige Orientierung an Branchen-tarifverträgen und alternative Formen der betrieblichen Mitarbeitervertretung haben die allgemeine Erosion etwas abgemildert. Multivariate Analysen zeigen, dass das traditionelle deutsche Modell der Arbeitsbeziehungen (mit Tarifverträgen und Betriebsräten zugleich) wahrscheinlicher in größeren und älteren Betrieben zu finden ist, während seine Existenz in eigentümergeführten und in Einzelbetrieben, in Ex-portbetrieben und in Betrieben im ausländischen Eigentum weniger wahrscheinlich ist. Allerdings gab es 2015 in mehr als 60% der deutschen Betriebe weder eine Tarifbindung oder -orientierung noch irgendeine Form der Mitarbeitervertretung. Ein solches Fehlen der Hauptinstitutionen des deutschen Modells der Arbeitsbeziehun-gen zeigt sich vor allem in kleinen und mittleren Betrieben, im Dienstleistungssektor und in Ostdeutschland, und das Ausmaß dieser Lücken steigt dramatisch an.
Keywords: J50; J52; J53; 330; collective bargaining; bargaining coverage; works council; worker participation; industrial relations; Germany